Studies in the physiology of creatine and creatinine - Shapiro, B G (Division of Physiological Sciences, 2020)
The studies recorded in this thesis cover a wide portion of the field of creatine-creatinine metabolism. They involve a consideration of the problem of the origin of creatine, of the endocrine factors controlling its metabolism, and of the function of creatine and creatinine in the body. In order to obtain a true perspective of the place of these investigations in relation to the physiology of creatine as a whole, it is first necessary to review briefly what is known of the metabolism and function of the two substances. And, in view of the light they throw on these questions, consideration must also be given to the chemical constitution and distribution of creatine and creatinine.